Respon Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) Terhadap Pemberian Pupuk Organik Cair Limbah Air Rebusan Kedelai pada Berbagai Komposisi Media Tanam - Kunti Malikhata Salma; Nurlaila Fatmawati (Journal of Horticulture Production Technology, 2026)
The production of pakcoy (Brassica rapa L.) has declined due to improper fertilization practices and limitations in growing media. Soybean boiling water waste has the potential to pollute the environment; however, it can be utilized as a liquid organic fertilizer (LOF) because it contains essential nutrients. This study aimed to determine the growth and yield response of pakcoy plants and to identify the best combination of LOF concentration and growing media composition. The research was conducted from October to January 2026 in Banjarnegara using a factorial Randomized Complete Block Design (RCBD) with two factors. The first factor was LOF concentration (P0, P1, P2, P3), and the second factor was the composition of growing media (M0, M1, M2, M3). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at 5%. The results showed a significant interaction (P < 0.05) on several parameters. The combination of P2M3 produced the highest shoot dry weight (26.45 g) and root length (22.17 cm), while the highest root fresh weight was observed in P2M1 (8.67 g). It can be concluded that soybean waste-based LOF at a moderate concentration combined with a higher proportion of cocopeat media enhances the growth and yield of pakcoy. This implies that soybean waste has strong potential as an environmentally friendly fertilizer for sustainable cultivation.